Drug‐Induced Skin Lesions of Bilateral Lower Extremities in an Elderly Patient With Poorly Controlled Diabetes - Jie Chen; Hua Wang; Linxuan Gu; Xiwen Zhu; Bangtao Yao (Clinical Case Reports, 2026)
ABSTRACT This study described a rare case of an 83‐year‐old man diagnosed with drug‐induced skin lesions of bilateral lower extremities after continuous self‐administration with clobetasol propionate ointment for eczema. On admission, his skin was paper‐thin, peeling, dry, bruising, and swollen on both lower extremities. Topical clobetasol propionate was immediately discontinued. During a 2‐week follow‐up period, his symptoms had resolved significantly.